Comparison of Selection and Long-term Clinical Outcomes Between Chemotherapy and Radiotherapy as Primary Therapeutic Modality for Ocular Adnexal MALT Lymphoma() - Jeon, Young-Woo (EClinicalMedicine, 2018)
BACKGROUND: The choice of a primary treatment for ocular adnexal mucosa-associated lymphoid tissue lymphoma (OAML) depends on the extent of tumor spread. However, radiotherapy is commonly used as a first-line therapy despite ophthalmic complications, because most OAMLs are in a limited stage of progression. However, the initial therapeutic modality, including chemotherapy and treatment of the advanced stage, has not been fully established for OAML. Therefore, we evaluated the optimal therapeutic options and survival outcome-related parameters for patients with primary OAML. METHODS: We evaluated 208 consecutive patients with primary OAML who were diagnosed at the Catholic University Lymphoma Group between January 2004 and April 2015. FINDINGS: During a median follow-up of 70.0 months (range, 3.2–182.0 months) in 208 patients with primary OAML, most patients were female and the median age was 46 years old. Overall survival (OS) and progression-free survival (PFS) at 13 years were excellent (92.7% and 69.7%, respectively). Of the 117 patients who received the first-line radiotherapy, 92% achieved complete remission (CR), usually by being treated with less than 30 Gy. Radiation-related ophthalmic complications including dry eye syndrome (59%) and cataract (22%) caused a decline in the quality of life (QoL). Chemotherapy alone was used to treat 86 OAML patients, with 84.9% achieving CR and 12.8% achieving partial remission with tolerable toxicities. There were no differences in survival outcomes between patients treated with radiotherapy versus those treated with rituximab-containing chemotherapy, although the latter group had more advanced stages of OAML (OS, p = 0.057; PFS, p = 0.075). INTERPRETATION: OAML patients were predominantly female and relatively young, and radiotherapy as a primary therapeutic option was more likely to lead to radiation-related complications, resulting in lower QoL. On the other hand, frontline chemotherapy showed consistent therapeutic outcomes with tolerable toxicities compared to radiotherapy, and there were no long-term or delayed adverse events. Therefore, when considering therapeutic efficacy and therapy-related QoL, chemotherapy is recommended for younger patients, and radiotherapy is recommended for older and chemotherapy-ineligible patients. FUNDING: A National Research Foundation of Korea (NRF) grant funded by the Korean government (MSIP) (No. NRF-2016R1A2B4007282).